THE EFFECTIVENESS OF COUNSELING USING BOOKLETS ON WUS KNOWLEDGE ABOUT CERVICAL CANCER IN MIDWIVES M KAMPUNG TENGAH KRAMAT JATI - Zulaika Zulaika; Dyah Chadariyanti (Jurnal Kesehatan, 2024)
According to WHO, cancer is the leading cause of death in the world, including Indonesia. The cancers that cause the highest female mortality in Indonesia are cervical cancer and breast cancer. Based on Riskesdas (Basic Health Research), 2013 reported the prevalence of tumors/cancer in Indonesia is 1.4 per 1000 population. The cause of cervical cancer is not known with certainty, efforts to detect cervical cancer one of them is by early detection with an IVA test. But there are still many women who are less aware of the importance of early detection of cervical cancer. The cause of the low IVA test is that knowledge is still low, resulting in less awareness to do IVA. This was revealed by Nuryati (2020) in obtaining a greater proportion of WUS who are knowledgeable found in WUS who do not conduct IVA test (24.4%) than those who do IVA test (6.7%). A knowledgeable WUS is 3.29 less likely to have an IVA test checked than a well-informed WUS. Research Methods used quantitative analytical research with Quasi Experiment design, one group pretest-posttest research design with control group, the subject group was measured once at the beginning (Pretest) before intervention (treatment) and after that re-measurement was carried out at the end ( Post test). The population in this study was all WUS mothers in Midwife M Kampung Tengah Kramat Jati, East Jakarta as many as 33 people, and the sample of this study amounted to 33 people consisting of intervention group people and the control group person. Data collection with questionnaires, data analysis with Wilcoxon and Mann-Whitney. Result that there is a positive influence between the results of knowledge and attitudes before and after counseling. There were 33 positive data which means that there were 33 mothers who experienced an increase in knowledge and a change in attitude from pre-test scores to post-test scores, with an average increase of 17, while the positive rank was 561. Based on the results of statistical tests, it is known that the P Value is 0.000. P Value <0.05. This means that there is a difference between the value of knowledge before and after counseling is given, so it can be concluded that there is an influence of counseling by using on knowledge. Counseling with booklets can increase maternal knowledge of cervical cancer. Advice on doing counseling with booklet media is a good tool in carrying out health promotion because it is very effective in increasing knowledge.